MAKNA DAN FUNGSI ADVERBIA DOUMO DALAM KOMIK BAHASA JEPANG - Virgiawan, Rydho (Universitas Negeri Jakarta, 2023)
Abstract : The purpose of this paper is to find out the meaning and function of the adverb doumo (どうも) in Japanese comics. This is motivated because the word doumo (どうも) when translated has several meanings and several functions in Japanese sentences. The meaning and function of the adverb doumo in comics is analyzed based on the theory put forward by Nakamichi (1991) in Koike, Tobita and Asada (1994) in Koike, and Mulya (2013). The method used in making this paper is descriptive qualitative method. The results of the study show that all the adverb functions doumo (どうも) appear in the comic except for the interjection function (どうもね). Meanwhile, the meaning and function of the adverb doumo (どうも) is determined based on the context of the sentence. From the results of the analysis, the most frequent meanings and functions of doumo (どうも) are expressing gratitude, expressing apologies, expressing indifference and as a casual expression of greeting.